Kelangkaan minyak bumi yang dapat menghambat jalannya perekonomian masyarakat di Daerah Jawa Timur - Wulan Suci, Nur (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2024)
Petroleum is natural resources consisting of plant and animal remains buried or deposited by mud. Petroleum is also one of the natural resources that cannot be renewed, such as kerosene, diesel oil and fuel oil. In this journal, the author aims to analyze the problem of oil scarcity in East Java. This study uses a research approach with qualitative methods. Journals are theoretical and conceptual journals that intend to find as many theoretical facts as possible so that the writer analyzes and draws conclusions. The results of this analysis indicate that the scarcity of petroleum can cause the economy to run slowly and irregularly. Based on the analysis of this research, it is hoped that the community, government, and other elements can conserve and protect natural resources properly so that there is no scarcity of petroleum. So that people's lives will be more prosperous.